A turning point for literacy : adult education for development :the spirit and declaration of Persepolis, Proceedings of the International Symposium for Literacy, Persepolis, Iran 3 to 8 September 1975 - International Symposium for Literacy (1975 : Persepolis); Bataille, Leon, editor (Oxford : PERGAMON PRESS, 1976)
Includes bibliographical references